Salivary cortisol concentration after high-intensity interval exercise: Time of day and chronotype effect. (3rd July 2017) - Bonato, Matteo; La Torre, Antonio; Saresella, Marina; Marventano, Ivana; Merati, Giampiero; Vitale, Jacopo Antonino
ABSTRACT: Due to personal and working necessities, the time for exercise is often short, and scheduled early in the morning or late in the afternoon. Cortisol plays a central role in the physiological and behavioral response to a physical challenge and can be considered as an index of exercise stress. Therefore, the aim of this study was to evaluate the influence of the circadian phenotype classification on salivary cortisol concentration in relation to an acute session of high-intensity interval exercise (HIIE) performed at different times of the day. Based on the morningness–eveningness questionnaire, 12 M-types (N = 12; age 21 ± 2 years; height 179 ± 5 cm; body mass 74 ± 12 kg, weekly training volume 8 ± 1 hours) and 11 E-types (N = 11; age 21 ± 2 years; height 181 ± 11 cm; body mass 76 ± 11 kg, weekly training volume 7 ± 2 hours) were enrolled in a randomized crossover study. All subjects underwent measurements of salivary cortisol secretion before (PRE), immediately after (POST), and 15 min (+15 min), 30 min (+30 min), 45 min (+45 min) and 60 min (+60 min) after the completion of both morning (08.00 am) and evening (08.00 p.m.) high-intensity interval exercise. Two-way analysis of variance with Tuckey's multiple comparisons test showed significant increments over PRE-cortisol concentrations in POSTcondition both in the morning (4.88 ± 1.19 ng · mL −1 vs 6.60 ± 1.86 ng · mL −1, +26.1%, P < 0.0001, d > 0.8) and in the evening (1.56 ± 0.48 ng · mL −1 vs 2.34 ± 0.37, +33.4%, P = 0.034, d > 0.6) exercise in all the 23 subject that performed the morning and the evening HIIE. In addition, during morning exercise, significant differences in cortisol concentration between M-types and E-types at POST (5.49 ± 0.98 ng · mL −1 versus 8.44 ± 1.08 ng · mL −1, +35%, P < 0.0001, d > 0.8), +15 min (4.52 ± 0.42 ng · mL −1 versus 6.61 ± 0.62 ng · mL −1, +31.6%, P < 0.0001, d > 0.8), +30 min (4.10 ± 1.44 ng · mL −1 versus 6.21 ± 1.60 ng · mL −1, +34.0%, P < 0.0001, d = 0.7), + 45 min (3.78 ± 0.55 ng · mL −1 versus 5.80 ± 0.72 ng · mL −1, +34.9%, P < 0.0001, d = 0.7), and + 60 min condition(3.53 ± 0.45 ng · mL −1 versus 5.78 ± 1.13 ng · mL −1, 38.9%, P = 0.0008, d = 0.7) were noted. No statistical significant differences between M-types and E-types during evening HIIE on post-exercise cortisol concentration were detected. E-types showed a higher morning peak of salivary cortisol respect to M-types when performing a HIIE early in the morning and produced higher salivary cortisol concentrations after the cessation of the exercise. Practical applications suggest that it is increasingly important for the exercise professionals to identify the compatibility between time of day for exercising and chronotype to find the individual's favorable circadian time to perform a HIIE.